(3JhVjM GdebGUOs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ dg , hUdhGJg Ydi eMeO NjQ fHi CQSdg hHYO agPG hVjM GdebGUO Cdajg GHf eGdc SMd eYGfjgG hjXgQ eMGSfgG , SCdfjI HYV MaGXgG GdeYfjjf HESJHGW ahGFOgG s
(3BNQgG (B:s
(3jfJgi HHGH GdCOZGe s
(3fSNI bOjeI fajSIs
(3LRA efgG ecJhH HGdMeQI hGdNVQIs
(3GdeNWhW eQbe GdUaMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B152s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs